Alum: An Efficient Catalyst for Trimethylsilylation of Alcohols and Phenols with Hexamethyldisilazane - Yang, Xiaojuan; Liang, Jinying (Asian Journal of Chemistry, 2011)
A highly convenient method for the trimethylsilylation of alcohols and phenols via treatment by hexamethyldisilazane in the presence of alum as a catalyst has been developed. A wide variety of hydroxyl groups were selectively protected in CH3CN under mild conditions.